PENGARUH CURRENT RATIO, RETURN ON ASSET DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL - Skolastika Dwi Febria; Rizki Pratomo Sunarwibowo (LPPM Politeknik Pratama, 2024)
The purpose of this study is to analyze the influence of the Current Ratio, Return on Assets, and Asset Structure on Capital Structure. This study used secondary data, with a total sample of 9 agricultural sector companies listed on the Indonesia Stock Exchange for the period 2017–2021. The data analysis technique used in this study is purposive sampling. The analysis tool employed is multiple linear regression analysis, using the Statistical Package for the Social Sciences (SPSS) version 25. The results of this study indicate that Return on Assets and Asset Structure have a negative and significant effect on Capital Structure. However, the Current Ratio has no effect on Capital Structure.